Antibacterial Activity of Propolis Supplemented-Chewing Candy Against Streptococcus mutans - I MADE ARTIKA; HARYANTO SUSILO; ADINDA VIRGINIA DWI SETYO; AHMAD ENDANG ZAINAL HASAN (Microbiology Indonesia, 2011)
Streptococcus mutans is considered to play a major etiological role in development of human dental plaque believed to related to dental caries, the most prevalent disease of the human oral cavity.  The objectives of the present study were to formulate and produce propolis supplemented-chewing candy and to investigate its antibacterial activity against S. mutans.  Propolis is a natural resinous bee-hive product thought to have antimicrobial, anti-inflammatory and immunostimulating activities.  Propolis was extracted from hives of bees of Trigona spp. using ethanol.   The extract was coated with maltodextrine and homogenized to generate propolis microparticles.  The particles were introduced into chewing candy preparations for the production of propolis supplemented-chewing candy.  The candy was then subjected to  in vitro antibacterial assays to test its activity against S. mutans isolated from human dental plaque.  Results showed that the ethanol extracted propolis of Trigona spp. bee-hives can be homogenized to form propolis microparticles.  The propolis microparticles could be used as a supplement in the formulation of chewing candy preparations.  The propolis supplemented-chewing candy showed antibacterial activity against S.  mutans. The candy, therefore, has the potential to be used as an antiplaque agent for prevention of dental caries.